2017
DOI: 10.1542/pir.2016-0134
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Adolescent Oral Health: A Review

Abstract: Oral health is one of the most unmet health care needs of adolescents. Oral disease can have a profound effect on overall health, including pain, missed school, heart disease, and even death. Adolescents have specific needs pertaining to oral health in addition to the usual lifelong issues of caries management, sports injury prevention, and dental referrals. Teen years are a higher risk time for oral piercings, increased sugar intake, nicotine initiation, and orthodontic considerations. Adolescents need a uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 12 publications
1
56
0
1
Order By: Relevance
“…Therefore, given that dental care is universally available in the country, parents’ education stands out as a major predisposing factor for dental services use for the very young. As a child grows older, their potential for visiting a dentist becomes better as they are able to clearly verbalise their needs, have more autonomy, and their needs for dental care are more unique and broader, beyond those of caries management and prevention. Therefore, to be able to utilise dental care effectively, they have to be predisposed and must have the means (enabling factors) to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, given that dental care is universally available in the country, parents’ education stands out as a major predisposing factor for dental services use for the very young. As a child grows older, their potential for visiting a dentist becomes better as they are able to clearly verbalise their needs, have more autonomy, and their needs for dental care are more unique and broader, beyond those of caries management and prevention. Therefore, to be able to utilise dental care effectively, they have to be predisposed and must have the means (enabling factors) to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed information found in literature [11][12][13][14] describing how oral piercings are the cause of a series of complications, such as dental abrasions, dental fractures, gingival recessions and loss of attachment of periodontal tissues, but also problems related to temporomandibular joint, as stated by Mejersjö in 2016 [15]. It is therefore necessary to establish education programs in schools between dentistry students and dentists themselves, in order to prevent the aforementioned complications reported, respectively, by Silk H et al [16], Junco P et al [17] and McGeary SP et al [18].…”
Section: Discussionmentioning
confidence: 99%
“…9 These individuals are in constant biological, psychological, and social development, and oral health interventions in this phase are able to instigate positive habits that can continue in adulthood. 10 Several studies, however, have demonstrated that Brazilian adolescents have a high dental treatment needs 11 and tend to report relative poor oral health and a low OHRQoL in terms of oral symptoms, functional limitations, and emotional and social well-being. [12][13][14][15] Hence, there is scarce information on how dental treatment could help to improve the adolescents' OHRQoL, [16][17][18][19] and on how adolescents experience quality of life.…”
Section: Introductionmentioning
confidence: 99%